Clonal variations and effects of juvenile wood on lumber quality in Japanese larch. Issue 2 (4th March 2022) - Tumenjargal, Bayasaa; Ishiguri, Futoshi; Iki, Taiichi; Takahashi, Yusuke; Nezu, Ikumi; Otsuka, Kouhei; Ohshima, Jyunichi; Yokota, Shinso
ABSTRACT: Wood properties, including Young's modulus, differ among clones in Larix kaempferi ; however, available information is still limited on among-clonal variations of lumber qualities in L. kaempferi . The objectives of this study were to clarify the clonal variations in lumber quality and to identify the effects of juvenile wood on lumber quality in L. kaempferi . A total of 21 logs of 2.5 m in length were obtained from the trees of nine different plus clones of 57-year-old L. kaempferi trees. The logs were sawn into lumber, and the lumber was kiln-dried and planed into 38 × 89 mm in a cross-section. Lumber quality, such as bending properties, was determined. Significant differences were found in wood density, dynamic Young's modulus, modulus of elasticity, and modulus of rupture of the lumber among the nine clones. The highest repeatability was recorded in wood density. The lumber consisting of juvenile wood showed a lower lumber quality compared to the lumber consisting of mature wood. To produce lumber with a high quality from L. kaempferi, the clonal variation of lumber quality and the existence of juvenile wood should be considered.